2018
DOI: 10.1002/ece3.4273
|View full text |Cite
|
Sign up to set email alerts
|

Testing the AC/DC hypothesis: Rock and roll is noise pollution and weakens a trophic cascade

Abstract: Anthropogenic sound is increasingly considered a major environmental issue, but its effects are relatively unstudied. Organisms may be directly affected by anthropogenic sound in many ways, including interference with their ability to detect mates, predators, or food, and disturbances that directly affect one organism may in turn have indirect effects on others. Thus, to fully appreciate the net effect of anthropogenic sound, it may be important to consider both direct and indirect effects. We report here on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…Recently, Barton et al. () have experimentally demonstrated the cascading effect of noise pollution along a beetle–aphid–plant tri‐trophic food chain but, to our knowledge, this is the only study to formally address this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Barton et al. () have experimentally demonstrated the cascading effect of noise pollution along a beetle–aphid–plant tri‐trophic food chain but, to our knowledge, this is the only study to formally address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…larvae are natural predators of water fleas (Pastorok, 1981) and the reduced vulnerability to fish predation under elevated noise level might have a negative indirect effect on water fleas. Recently, Barton et al (2018) have experimentally demonstrated the cascading effect of noise pollution along a beetle-aphid-plant tri-trophic food chain but, to our knowledge, this is the only study to formally address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Basal resource survivorship will be determined by how sensory stress affects intermediate prey ability to locate basal resources in these situations. For example, anthropogenic noises reduce lady beetle predation rates on aphids by potentially disrupting vibration detection of prey but does not affect aphid reduction of plant biomass, and consequently, aphids are released from top‐down lady beetle effects in the presence of noise pollution (Barton et al., 2018). Thus, estimates of the sensory performance of both predators and prey across the same gradient provide a framework to understand how sensory stress may structure communities by changing cascading predator effects.…”
Section: Discussionmentioning
confidence: 99%
“…In these scenarios it is predicted that consumptive effects will decrease in strength as sensory stress increases and predation-risk effects will remain important until the point at which prey detection of predators begins to decline (Weissburg et al, 2014). from top-down lady beetle effects in the presence of noise pollution (Barton et al, 2018). Thus, estimates of the sensory performance of both predators and prey across the same gradient provide a framework to understand how sensory stress may structure communities by changing cascading predator effects.…”
Section: Discussionmentioning
confidence: 99%
“…It will also be important to predict the behavioural changes of more than just one species in the interaction. For instance, predators may be less effective under noise (Barton et al, 2018), which may dampen the increase in prey vulnerability. Richer game theoretic models are necessary to predict these outcomes (McNamara, 2013).…”
Section: Discussionmentioning
confidence: 99%